Effect of transglutaminase on the quality of yoghurt made with different milk protein sources - Yara, A. Husein; Aita, O.A.; Fayed, Atia.; El-Nawawy, M.A. (2006)
Cow's milk was fortified with 0.5, 1.0 or 1.5 % milk protein supplied either from skim milk powder (SMP), sodium caseinate (NaCn), dried whey protein concentrate (WPC), or by concentrating the milk through the ultrafiltration process and treated with TG at a level of 0.5 g/l.
Includes reference.
Summary in Arabic.
1
Keywords: Dairy products; Transglutaminases; Yogurt industry; Skim milk -- Composition; Dried milk